An alternative approach for the sediment control of in-channel stony debris flows with an application to the case study of Ru Secco Creek (Venetian Dolomites, Northeast Italy) - Barbini, Matteo; Bernard, Martino; Boreggio, Mauro; Schiavo, Massimiliano; D’Agostino, Vincenzo; Gregoretti, Carlo (Frontiers in Earth Science, 2024)
The sediment control for reducing the debris-flow hazard is generally approached using retention basins that can be closed or have an outlet structure, generally an open check dam. They are usually placed in mild slope zones that allow the minimum works for the excavation and the foundation of the outlet structure if present. Recently, it has been shown that the storage of sediments can also be achieved in the high-sloping reaches of debris-flow channels by means of deposition areas, basins that are open on the downstream side. Therefore, in this work, we propose an approach for the control of the sediment volume transported by debris flows consisting of a cascade of deposition areas and retention basins. We also include a framework for the planning, sizing and checking of the works. Two scenarios are considered, corresponding to the maximum values of the debris-flow peak discharge and volume, respectively. Moreover, the presence or absence of boulders is also considered. For this purpose, a method that evaluates the clogging of a single open check dam as a function of the coarse fraction of the sediment volume is simply extended to the case of multiple dams and implemented in a routing model. The proposed approach is applied along the Ru Secco Creek (northeast Italy) for the purpose of defending, from the debris-flow hazard, a resort area and a village hit in 2015 by a high-magnitude debris flow. After a careful survey and the study of the basin, a solution with a combination of deposition areas and retention basins is planned and sized. The validity and performance of the proposed solution are analyzed by means of debris-flow modelling for the two scenarios, considering both the absence and presence of boulders. Most of the sediment volume transported by debris flows is trapped and a small solid discharge flows downstream of the works.